Diversity of Filamentous Fungi Isolated From Some Amylase and Alcohol-Producing Starters of India - Anupma, Anu; Tamang, Jyoti Prakash (Frontiers in Microbiology, 2020)
Abstract Filamentous fungi are important organisms in traditionally prepared amylase and alcohol-producing dry starters of India. We collected 40 diverse types of amylase and alcohol-producing starters from eight states of North East India viz. marcha, thiat, humao, hamei, chowan, phut, dawdim and khekhrii. Average fungal population was 4.9 x 105 cfu/g with average pH 5.3 and 10.7 %, respectively. In present study, 131 fungal isolates were isolated and characterised based on macroscopic and microscopic characteristics and grouped into 44 representative fungal strains. Based on results of morphological characteristics and ITS gene sequencing, 44 fungal strains were grouped into 3 phyla represented by Ascomycota (48%), Mucoromycota (38%) and Basidiomycota (14%). Taxonomical keys to species level was illustrated on the basis of morphological characteristics and ITS gene sequencing aligned to fungal database of NCBI GenBank which showed 7 genera with 16 species represented by Mucor circinelloides (20%), Aspergillus sydowii (11%), Penicillium chrysogenum (11%), Bjerkandera adusta (11%), Penicillium citrinum (7%), Rhizopus oryzae (7%), Aspergillus niger (5%), Aspergillus flavus (5%), Mucor indicus (5%) Rhizopus microsporus (5%), Rhizopus delemar (2%), Aspergillus versicolor (2%), Penicillium oxalicum (2%), Penicillium polonicum (2%), Trametes hirsuta (2%) and Cladosporium parahalotolerans (2%). The Shannon diversity index H was recorded highest in marcha of Sikkim (H: 1.74) and lowest in hamei of Manipur (H: 0.69). Fungal species present in these amylolytic starters are morphologically, ecologically and phylogenetically diverse and showed high diversity within the community.